Investigating the Efficacy of Behavioral Models to Predict Use of Health Technology: A Scoping Review. (September 2022) - Zahed, Karim; Fields, Sherecce; Sasangohar, Farzan
Chronic conditions are widespread and need serious behavioral habits to manage or mitigate. There is a gap in understanding the role of beliefs to assess intention to use and to sustain using technology that can aid in performing healthy behaviors. This review aims to understand the common behavioral models used in the literature to understand intention to use health-related technologies. The scoping review included 36 articles, and results show that integrating constructs from more than one behavioral model may add to the capability of behavioral models to predict intention. The research also shows that intention needs to be assessed longitudinally and compared with actual behavior performed to capture a realistic assessment of the relationship between intention and action.